Are banks excessively monitored? - Urs W. Birchler (Swiss National Bank, Study Center Gerzensee, 2000)
Insufficient monitoring by depositors, and thus a lack of market discipline, are often seen as a typical feature of banks. We show that the opposite may be the case. Banks, defined as fims that borrow from a large number of partially uninformed investors, have a tendency to be excessively monitored by informed investors. This is shown in a model of intermediation in which heterogenous investors choose whether they want to monitor the intermediary or not. We also find that bank finance is preferable to non-bank finance when assets are relatively safe or opaque. The model which is set in a banking context may be applicable to a wider range of information problems.
Keywords: 330; Einlagensicherung; Theorie